2021
DOI: 10.1159/000517969
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends in the Treatment of Mild Ischemic Stroke with Intravenous Thrombolysis: Paul Coverdell National Acute Stroke Program

Abstract: <b><i>Background:</i></b> Presentation with mild symptoms is a common reason for intravenous thrombolysis (IVT) nonuse among acute ischemic stroke (AIS) patients. We examined the impact of IVT on the outcomes of mild AIS over time. <b><i>Methods:</i></b> Using the Paul Coverdell National Stroke Program data, we examined trends in IVT utilization from 2010 to 2019 among AIS patients presenting with National Institutes of Health Stroke Scale (NIHSS) scores ≤5. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Numerous studies have reported the racial disparity in IVT utilization rate [1,10,11,37,38]. We observed the same phenomenon (7% in non-white vs. 13% in white; p = 0.042), which was not surprising given the delay in ED arrival in the case of the non-white group.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have reported the racial disparity in IVT utilization rate [1,10,11,37,38]. We observed the same phenomenon (7% in non-white vs. 13% in white; p = 0.042), which was not surprising given the delay in ED arrival in the case of the non-white group.…”
Section: Discussionsupporting
confidence: 80%